69.9k views
3 votes
Consider the expression –4b + 8c + 12 – 8b – 2c + 6. Part A Simplify the expression. b + c + Part B Factor the simplified expression using the GCF. 2(–2b + c + 3) 3(–2b + c + 3) 4(–2b + c + 3) 6(–2b + c + 3) Part C What is the value of the expression when b = 2 and c = –3?

2 Answers

1 vote

Answer:

3

Explanation:

User Natrium
by
5.7k points
3 votes

Answer:

Explanation:

Given the expression

-4b + 8c + 12 – 8b – 2c + 6.

To simplify, first collect the like terms

= (-4b-8b)+(8c-2c)+(12+6)

= -12b+6c+18

Factor out the GCF

The GCF is 6

On factoring out;

= 6(-2b+c+3)

If b = 2 and c = -3 the expression becomes:

= 6(-2(2)+(-3)+3)

= 6(-4-3+3)

= 6(-4+0)

= 6(-4)

= -24

Hence the value of the expression when b = 2 and c = -3 is -24

User Khanou
by
4.6k points